The concept of twin digital models as support for production and service processes of technical facilities - Simiński, Przemysław (Studia Informatica. System and information technology, 2023)
The article presents the concept of using twin digital models as support for production and service processes of technical facilities. The implementation of the concept can be helpful in diagnostic processes and proactively diagnose the condition of technical objects in real time and report actions to ensure the continuity of processes. The concept assumes the creation of a digital model of a technicalobject for the purposes of improving the operation processes of the machine park (means of transport, means of production). A comprehensive and integrated solution will improve work efficiency and lower service costs.